What is The Comparative Effectiveness of Conservative Management versus Surgical Repair For Patients with Traumatic Kidney Injuries? : A Systematic Review - Ilham Akbar A.R; I Gusti Agung Ngurah Maha Yudha; Moza Farijah Qaulika; Zata Sabrina (International Medical Journal Corp. Ltd, 2025)
Introduction: The management of traumatic kidney injuries has increasingly shifted towards non-operative management (NOM), yet its comparative effectiveness against surgical repair, particularly in high-grade cases, requires ongoing clarification. This systematic review was conducted to evaluate and synthesize the existing evidence on the comparative effectiveness of conservative management versus surgical repair for patients with traumatic kidney injuries, focusing on key outcomes such as mortality, renal preservation, and complications. Methods: This systematic review adhered to PRISMA 2020 guidelines. A comprehensive search was performed across PubMed, Springer, Google Scholar, Semantic Scholar, and Wiley Online Library to identify relevant studies. Studies were included if they involved human patients with traumatic kidney injuries and compared conservative and/or surgical interventions. Following the screening and eligibility assessment, 29 studies were included in the final analysis. Results: The findings overwhelmingly favor NOM for hemodynamically stable patients. Mortality rates for conservative management were consistently lower (most under 10%) compared to surgical repair (most over 10%). Renal preservation rates were substantially higher with NOM (frequently exceeding 85%) , while renal loss in surgical cohorts was significantly greater. Complication rates were also lower in the NOM groups (2-32%) versus surgical groups (10-76%). Even for high-grade injuries (AAST III-V), NOM was the preferred initial approach in stable patients , with angioembolization identified as a key technique for improving outcomes. Discussion: The evidence demonstrates that the primary determinant for management is the patient's hemodynamic stability, not the grade of injury alone. Surgical intervention, while vital for hemodynamically unstable patients, carries higher risks of morbidity and mortality in stable populations. The integration of angioembolization has been pivotal to the success of NOM, allowing for hemorrhage control while preserving renal parenchyma. Conclusion: Non-operative management is the established standard of care for hemodynamically stable patients across all grades of traumatic kidney injury. This strategy is associated with improved survival, superior organ preservation rates, and fewer complications. Supported by minimally invasive techniques like angioembolization, the conservative approach has successfully minimized patient morbidity and reduced unnecessary nephrectomies.